Microfinance as a suitable instrument of European and Czech development cooperation - Karel SRNEC; Jiřina SVITÁKOVÁ; Magdalena VÝBORNÁ; Pavel BURIAN (Agricultural Economics (AGRICECON), 2011)
European countries use microfinance as an instrument of development cooperation in three separate forms, which differ in the financial flow. In the first type, the government transfers grant money to their non-government organizations (NGOs), which then distribute the funds directly to the local microfinance institutions (MFIs) (eg. Finland). In the second form, the funds are sent through to the branch-offices of the NGOs located in the developed country to developing countries (eg. Norway, Sweden). The third type allows for a direct relationship between a donor country development co-operation agency and a local microfinance institution in a developing country without intermediation of the developed country NGOs (eg. Great Britain, Germany). The Czech Republic currently does not support microfinance by the direct/indirect transfer of funds, but it promotes the awareness of the Czech NGOs and the public of microfinance as a tool for the economic development.